A particular frozen yogurt has 75 cal in 2 ounces how many calories are in 8 ounces of the yogurt

Answers

Answer 1
Answer:

Total number of calories in 8 ounce yogurt is 300 calories.

Given that;

Total number of calories in 2 ounce yogurt = 75 calories

Find:

Total number of calories in 8 ounce yogurt

Computation:

Total number of calories in 8 ounce yogurt = 75[8/2]

Total number of calories in 8 ounce yogurt = 75[4]

Total number of calories in 8 ounce yogurt  = 300 calories

Learn more:

brainly.com/question/22374134?referrer=searchResults

Answer 2
Answer: Just divide 8 by 2 and you'll get 4
Each container is 2 ounces so do 75 times 4 and you'll get 300 calories

Related Questions

Which equation represents the vertical line passing through (7,-3)A. x=-3B. y=-3C. x=7D. y=7
given: km and jn bisect each other. do triangle jkl and triangle nml meet SAS criteria.. NEED DESCRIPTION
PLEASE HELP, DUE AT MIDNIGHT >>>>>
BY using eight eights  and addition only can you make 1000?????/
You and your friend are rolling number cubes. Each cube has 6 sides with the numbers 1 to 6. If a sum of 7 is rolled, your friend gets a point. However, you get a point if either one of the sums listed below is rolled. Which pair of numbers would make the game fair?

Um so how would you treat a big open wound that u can not put a bandaid on?

Answers

Answer:

wrap in gauze

Step-by-step explanation:

Solve the system of equations.6x – 3y = 3
–2x + 6y = 14
What number would you multiply the second equation by in order to eliminate the x-terms when adding to the first equation?

What number would you multiply the first equation by in order to eliminate the y-terms when adding to the second equation?

Answers

Keywords:

Systems of equations, variables, values, steps

For this case we have a system of two equations with two variables given by "x" and "y" respectively. We must solve the system by finding the values of the variables. For this, we follow the steps below:

6x - 3y = 3\ (1)\n-2x + 6y = 14\ (2)

Step 1:

We multiply the second equation by 3:

3 * (- 2x + 6y = 14)\n-6x + 18y = 42

Step 2:

We add both equations:

6x - 3y = 3\n-6x + 18y = 42\n-6x + 6x-3y + 18y = 42 + 3\n15y = 45

y = \frac {45} {15}\ny = 3

Step 3:

We substitutey=3 in the first equation:

6x - 3 (3) = 3\n6x-9 = 3\n6x = 3 + 9\n6x = 12\nx = \frac {12} {6}x = 2

Thus, the solution of the system is given by (x, y) = (2,3)

Answer:

The second equation must be multiplied by "3" to eliminate the terms of the "x" when added with the first equation

The first equation must be multiplied by "2" to eliminate the terms of the "y" when added with the second equation

The system solution is given by (x, y) = (2,3)

Which set of integers is included in (-1,3]?(1) {0,1,2,3} (3) {-1,0,1,2,3,4}
(2) {-1,0,1,2} (4) {-2,-1,0,1,2,3}

Answers

Hello,

N={0,1,2,3,4,5,...}

(-1,3]={0,1,2,3}⊂N

Answer (1) no negative whole numbers.

What type of line is the graph of x = −2?

Answers

X=-2 is vertical line
x=-2 would be a VUX line 

Choose the option that best completes the statement below. In finding the number of permutations for a given number of items, _____. A) the number of permutations is limited by the number of items which are alike.
B) it doesn’t matter if some of them are indistinguishable .
C) the number of permutations is determined by the number of items that don’t repeat.
D) the number of permutations isn’t dependent on the items that repeat.

Answers

Let’s look at the permutations of the letters “ABC.” We can write the letters in any of the following ways:
ABC
ACB
BAC
BCA
CBA
CAB
Since there are 3 choices for the first spot, two for the next and 1 for the last we end up with (3)(2)(1) = 6 permutations. Using the symbolism of permutations we have: 3 P_(3)=(3)(2)(1)=6. Note that the first 3 should also be small and low like the second one but I couldn’t get that to look right.

Now let’s see how this changes if the letters are AAB. Since the two As are identical, we end up with fewer permutations.
AAB
ABA
BAA
To make the point a bit better let’s think of one A are regular and one as bold A.
A
BA and ABlook different now because we used bold for one of the As but if we don’t do this we see that these are actual the same. If they represented a word they would be the same exact word.

So in this case the formula would be (3 P_(3) )/(2!)= ((3)(2)(1))/((2)(1))= (6)/(2)=3. We use 2! In the denominator because there are 2 repeating letters. If there were three we would use 3!


Hopefully, this is enough to let you see that the answer is A. The number of permutations is limited by the number of items that are identical.



4) -4x - 10.2
I need the answer to this question asap please.

Answers

Answer: -2.55

Explanation: First add 10.2, and then the equation becomes -4x = 10.2.

Then, you just divide by -4 from both sides of the equation, and you get x = -2.55. :]

Answer:

21 - 4x

Step-by-step explanation:

Multiply 10 and 2 to get 20.

41 - 4x - 20

Subtract 20 from 41 to get 21.

21 - 4x